Physical inactivity and chronic diseases among disabled adults in Indonesia - Tika Dwi Tama; Erni Astutik (AOSIS, 2022)
Physical activity is a recognized determinant in preventing non-communicable diseases. However, people with disabilities have more barriers to do physical activity. This study was conducted to assess the physical activity level of disabled adults in Indonesia and its association with chronic diseases. This cross-sectional study used secondary data from the Indonesian Family Life Survey (IFLS) wave 5. As many as 2927 adults with disabilities involved in this study. The International Physical Activity Questionnaires (IPAQ) was used to measure physical activity. Chronic diseases were assessed based on the diagnosed disease records. Univariate, bivariate, and multiple logistic regression were performed to analyse the data. The proportion of low physical activity among adults with disabilities reached 36.2%. The number of persons with disabilities who suffer from chronic diseases was 10.8%. Disabled adults with low physical activity had higher odds of getting chronic diseases than those with moderate-high physical activity (p-value = 0.04; aOR 1.43; 95% CI 1.12-1.84) after being controlled by other covariates. Engaging disabled persons according to the appropriate types of physical activity may reduce the risk of chronic diseases.